2017
DOI: 10.1007/s00334-017-0642-y
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-vegetation richness and diversity relationships in the tropics

Abstract: Tracking changes in biodiversity through time requires an understanding of the relationship between modern diversity and how this diversity is preserved in the fossil record. Fossil pollen is one way in which past vegetation diversity can be reconstructed. However, there is limited understanding of modern pollen-vegetation diversity relationships from biodiverse tropical ecosystems. Here, pollen (palynological) richness and diversity (Hill N 1 ) are compared with vegetation richness and diversity from forest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…A series of earlier studies have found similar positive correlations between pollen and plant richness in Europe (Birks, ; Felde et al, ; Matthias et al, ; Meltsov et al, ; Odgaard, ). However, investigations from the tropics (Gosling et al, ; Jantz, Homeier, & Behling, ) or from temperate western North America (Goring et al, ) have not found such positive correlations. Evaluating pollen–plant diversity relationships not only depends on the nature of pollen data but also on the spatial scale and quality of plant data (Birks, Felde, Bjune et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A series of earlier studies have found similar positive correlations between pollen and plant richness in Europe (Birks, ; Felde et al, ; Matthias et al, ; Meltsov et al, ; Odgaard, ). However, investigations from the tropics (Gosling et al, ; Jantz, Homeier, & Behling, ) or from temperate western North America (Goring et al, ) have not found such positive correlations. Evaluating pollen–plant diversity relationships not only depends on the nature of pollen data but also on the spatial scale and quality of plant data (Birks, Felde, Bjune et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Among the landscape variables, openness and elevation have positive correlations with pollen richness and, as discussed above, earlier studies have also shown that both variables can have a positive effect on pollen richness (but not necessarily through an increase in plant richness) (Felde et al, ; Meltsov et al, ; Odgaard, ). In two modern pollen–plant richness studies from the tropics, where there is no clear link between pollen and plant richness, the gradient of openness is involved: Gosling et al () described the diversity from closed evergreen forests to wooded savanna and Jantz et al () involved elevational gradients. Openness, at high elevations or latitudes, in naturally open dry areas or human‐influenced landscapes is known to have a positive effect on pollen richness through the increased pollen‐source area in open conditions (Felde et al, ; Seppä, ; Sugita et al, ) and through higher pollen evenness that allows more taxa to be detected (Odgaard, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations